Village Tourism as a Contextual Teaching and Learning Strategy for Creative Writing Development - Indri Jurikhe Pandie; Anas Ahmadi; Fithriyah Inda Nur Abida (DE FACTO : Journal Of International Multidisciplinary Science, 2026)
This study examines village tourism as an experiential and contextual learning model for developing students’ creative writing skills, especially poetry. It addresses limited integration of experiential learning theory, contextual teaching and learning (CTL), and creative writing pedagogy within one framework. Using a qualitative descriptive-analytical approach, the study analyzes four poems produced after village tourism activities. Analysis focuses on sensory imagery, originality, experiential learning processes, and CTL integration. Findings show that village tourism strengthens multisensory engagement and helps students transform rural experiences into poetic imagery. Students move beyond description by reinterpreting experience through metaphorical, symbolic, and introspective language, reflecting deeper cognitive and aesthetic processing. The results align with Kolb’s experiential learning cycle and demonstrate CTL principles through inquiry, reflection, and authentic assessment. Village tourism therefore functions as a learning ecosystem linking sensory experience, cognitive interpretation, and aesthetic transformation in higher education.